STUDI KINERJA KOLAM AERASI DI TPA TELAGA PUNGGUR KOTA BATAM DITINJAU DARI PARAMETER BOD5, COD, TSS DAN TDS - , ONELLA MARISKA, Dr. Ir. Sarto, M,Sc ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Leachate is one of problems existed in TPA Telaga Punggur. Leachate in TPA Telaga Punggur have been processed in the leachate treatment plant, one of unit process is using aerated Lagoon. Although it has been processed, there are still have some quality of leachate exceeds the quality standard in The Decree of The Minister of Environment no. 51 of 1995. The purpose of this study are: to know the ability of aerated lagoon in reducing pollutant of leachate, to know the efectiveness of aerated lagoon performance based on parameters BOD5, COD, TSS and TDS, and to provide recommendations of processing unit in processing leachate. In this study was carried out on the measurement of the quantity and quality of leachate in inlet and outlet aerated lagoon, then it will conducted analysis on the performance of aeration lagoon in reducing BOD5, COD, TSS and TDS. The results of this study are: aerated lagoon can reduce levels of TSS in the leachate, but it have not able to reduce levels of BOD5, COD and TDS, aerated lagoon has not effective in reducing BOD5, COD , TSS and TDS, due to aerated Lagoon only can reduce BOD5 levels of 5.97%, 4.35% of COD, TSS of 49.69% and TDS of 5.01%, the recommendation for processing leachate by using Advanced Oxidation process (AOP)